Üniversite öğrencilerinde dışavurumcu teknikler çerçevesinde tasarlanan yaşam anlamı grup çalışmasının yaşam anlamı, amaç bilinci ve depresyon düzeyine etkisinin incelenmesi - AYDOĞDU, BİLGE NURAN; ERYİĞİT, DERYA (My University, 2022)
Bu çalışmanın amacı üniversite öğrencilerine yönelik geliştirilen 8 haftalık yaşam anlamı grup çalışmasının etkililiğini test etmektir. Bireylerin yaşamdaki amaçlarına dair bilinçli oluşu, bir amaç belirlemiş oluşunun bireyin iyi oluşunu destekleyecek bir sistem sunacağı düşünülmektedir. Bu nedenle Marmara Üniversitesi Psikolojik Danışma ve Rehberlik Uygulama Araştırma Merkezi (MARPAM) üzerinden gerçekleştirilen duruyu sonucunda çalışmaya katılmaya gönüllü olan sekiz öğrenci ile grup oturumları düzenlenmiştir. Çalışmada ön test son test tek gruplu zayıf deneysel yöntem kullanılmıştır. Oturumlar öncesi katılımcılardan Yaşam Anlamı Ölçeği, Amaç Bilinci (Hissi) Ölçeği ve DAS-21 ölçeği Depresyon alt boyutu aracılığı ile verileri toplanmıştır. Öntest-sontest verileri arasındaki fark Wilcoxon İşaretli Sıralar testi ile SPSS-20 programında analiz edilmiştir. Katılımcılardan her oturum sonrasında toplanan açık uçlu sorulardan elde edilen veriler içerik analizi ile analiz edilmiştir. Yapılan analizler sonunda katılımcıların yaşam anlamı ölçeğinden, amaç bilinci ölçeğinden ve DAS-21 ölçeği depresyon alt boyutundan aldıkları ön test ve son test puanları arasındaki fark istatistiksel olarak anlamlı bulunmuştur. Söz konusu farklılık son testler lehine gerçekleşmiştir. Nitel verilerin analizinde katılımcıların yanıtlarının anlamlandırma, içsel yolculuk, farkındalık ve empati temaları etrafında şekillendiği görülmüştür.

The aim of this study is to test the effectiveness of expressive therapy program on university students’ meaning in life for eight sessions. An important aspect of psychological well-being, especially emphasized in humanist theories, is the perceived meaning in life. Purpose in life has been defined by Frankl as having goals and believing that life is fulfilling and worthwhile. It is considered that having an awareness about life goals and determining a goal will provide a system that will support the well-being of the individual. Therefore, group sessions were organized with the students reached through Marmara University Psychological Counseling and Guidance Application Research Center (MARPAM). In the study, a quasi-experimental method with a pretest-posttest experimental group was used. Before the sessions, the data were collected from the participants through the The Meaning in Life Questionnaire, Sense of Purpose Scale, and depression subscale of DASS-21 scale. The difference between data of pre-test and post-test was analyzed with the Wilcoxon Signed Ranks test in the SPSS-20 program. The data collected from the participants after each session through interviews including open-ended questions, were analyzed with content analysis. At the end of the analyzes, the difference between pre-test and post-test scores of the participants from the The Meaning in Life Questionnaire, Sense of Purpose Scale and the depression sub-dimension of the DASS-21 scale was found statistically significant at the level of p <.05. This difference occurred in favor of the post-tests. In the analysis of qualitative data, it was observed that the responses of the participants were shaped around the themes of interpretation, inner journey, awareness and empathy
The effect of meaning in life group sessions designed within the framework of expressive techniques on meaning in life, sense of purpose and depression levels of university students
Keywords: yaşam anlamı; amaç bilinci; depresyon; dışavurumcu sanat terapisi; üniversite öğrencileri; meaning in life; sense of purpose; depression; expressive art therapy; university students